Respuesta :

Answer:

The values are

x = -25/9 = -2 7/9

y = 7/3 = 2 1/3

Step-by-step explanation:

3x + 2y = -13 --------eqn 1

3x + 4y = 1-------------eqn2

Using eqn 2 to get the value of y

3x + 4y = 1

4y = 1 - 3x

Dividing both sides by 4,to get y

4y/4 =( 1 -3x) / 4

y = (1 - 3x) / 4

Since we've gotten the value for y, substitute the value into eqn 1

3x + 2y = -13

3x + 2(3x - 1)/4 = -13

Opening the bracket

3x + (6x - 2)/4 = -13

LCM = 4

(12x + 6x - 2) / 4 = -13

18x - 2 / 4 = -13

Then we cross multiply

18x - 2 = -13 * 4

18x - 2 = - 52

18x = -52 + 2

18x = -50

Divide both sides by 18, to get the value of x

18x/18 = -50/18

x = -25/9

or x = -2 7/9

The value of x is now known, so let's go back to eqn 2

Substitute x = - 25/9

3x + 4y = 1

3(-25/9) + 4y = 1

Open the bracket

-75/9 + 4y = 1

Make y the subject of the formula

4y = 1 + 75/9

LCM = 9

4y = (9 + 75)/ 9

4y = 84/9

To get y, divide both sides by 4

4y/4 = 84/9 / 4/1

y =

Note : when division changes to multiplication, it always be in its reciprocal form

y = 84/9 / 1/4

y = 84 * 1 / 9 *4

y = 84/ 36

y = 7/3

Or

y = 2 1/3